If it's not what You are looking for type in the equation solver your own equation and let us solve it.
f+2=9
We simplify the equation to the form, which is simple to understand
f+2=9
We move all terms containing f to the left and all other terms to the right.
+1f=+9-2
We simplify left and right side of the equation.
+1f=+7
We divide both sides of the equation by 1 to get f.
f=7
| 4h+24=6k-10 | | 12h+6=3(2+4h) | | .66x+18=90 | | -92=-6x+5(3x-4) | | 6u+6=8u+8 | | -(x-8)+3x=2(x+4) | | -22+15-22z=31 | | 33-2(16.5)= | | 15-w/4=-28 | | 160=9x+8x+10 | | r-10=14 | | 18-2(16.5)= | | 6(3d+2)-8=40 | | 4s+9=7x | | 2(-x+6)+4x-x=2x+8 | | 5z=65464 | | 18-2(16-5)= | | 3x-26=15+3x | | 2(y+1)+13=57 | | -6+4=-38 | | 2x-(4-3x)-9=x-(-4x-3)+8 | | -4(2-x)+5=12 | | .5x+1=5 | | 1+5x-40=7-1x | | 9x-7=7(2x-11) | | sin(2x)-cos(x)-(2sin(x))+1=0 | | 3x-2=45 | | 2(x+3)+7=10 | | 5z+8=7 | | 5x-17=-82 | | -8(7x-8)=456 | | -8(7x-8)=457 |